2022
DOI: 10.1111/1460-6984.12837
|View full text |Cite
|
Sign up to set email alerts
|

Insights into social communication following traumatic brain injury sustained in older adulthood

Abstract: BackgroundThere is a lack of evidence relating to cognitive‐communication difficulties following traumatic brain injury (TBI) sustained in older adulthood. A prominent area in which post‐TBI cognitive‐communication difficulties manifest is at the level of social communication. An investigation of social communication focusing on comparison of those injured in older and younger adulthood is a practical starting point for age‐related cognitive‐communication outcome comparison.AimsThe overall objective of this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…These findings offer new insights into factors contributing to impaired communication after TBI. Shorland et al (2022) note that age should also be considered as a factor in evaluating cognitive communication skills after TBI. The older adults (aged 50-70 at the time of injury) in their study reported a similar frequency of communication difficulty compared to the younger adults (aged 18-40 at the time of injury).…”
Section: The Complex and Chronic Nature Of Cognitive-communication Di...mentioning
confidence: 99%
“…These findings offer new insights into factors contributing to impaired communication after TBI. Shorland et al (2022) note that age should also be considered as a factor in evaluating cognitive communication skills after TBI. The older adults (aged 50-70 at the time of injury) in their study reported a similar frequency of communication difficulty compared to the younger adults (aged 18-40 at the time of injury).…”
Section: The Complex and Chronic Nature Of Cognitive-communication Di...mentioning
confidence: 99%